Academically Capable Students who are Failing in High School: Perceptions about Achievement - Ponsford, Kenneth R.; Lapadat, Judith C. (Canadian Journal of Counselling and Psychotherapy, 2007)
A sub-group of at-risk learners, familiar to high school counsellors, consists of students who have demonstrated academic capability yet begin to fail in their senior years. Although they do not fit within a high-risk profile, such students are at risk of not completing their secondary school education and may acquire inadequate preparation for post-secondary education or rewarding careers. Our goal was to describe the achievement perspectives of three such students from a small rural community, using qualitative interviews. We found that academic, social, family, and peer factors influenced their decision making. We suggest ways to modify school practices to provide better support for such students.